Effectiveness of Airway Management Strategies in Critically Ill Patients: A Meta-Analysis - Putra, Ricko Yorinda; Novita Anggraeni; Johannas (HM Publisher, 2024)
Background: Airway management is a cornerstone of critical care, but the optimal strategies for critically ill patients remain debated. This meta-analysis aimed to evaluate the effectiveness of various airway management techniques in critically ill patients. Methods: A systematic search of PubMed, Embase, Cochrane Library, and Web of Science was conducted from January 2018 to December 2023. Studies comparing different airway management strategies (e.g., endotracheal intubation, laryngeal mask airway, video laryngoscopy) in critically ill adults were included. Primary outcomes were successful airway establishment, time to airway securement, and complications (e.g., hypoxia, aspiration). Meta-analyses were performed using random-effects models, and the risk of bias was assessed. Results: Twenty-three studies (n=5,894 patients) were included. Video laryngoscopy was associated with a higher success rate of first-pass intubation compared to direct laryngoscopy (OR 1.85, 95% CI 1.43-2.40, p<0.001). No significant differences were found in overall complications between video laryngoscopy and direct laryngoscopy (OR 0.92, 95% CI 0.68-1.24, p=0.59). In patients with difficult airways, video laryngoscopy demonstrated a reduced risk of complications compared to direct laryngoscopy (OR 0.63, 95% CI 0.41-0.97, p=0.04). Conclusion: Video laryngoscopy is a safe and effective alternative to direct laryngoscopy, particularly in critically ill patients with predicted difficult airways. Further research is needed to determine the optimal airway management strategy in specific subgroups of critically ill patients.